2004
DOI: 10.1007/s00240-004-0432-8
|View full text |Cite
|
Sign up to set email alerts
|

Phyllanthus niruri normalizes elevated urinary calcium levels in calcium stone forming (CSF) patients

Abstract: Phyllanthus niruri is a plant used for years in Brazil to treat urinary calculi. We prospectively evaluated the effect of P. niruri intake on 24 h urinary biochemical parameters in an attempt to assess its in vivo effect in calcium stone forming (CSF) patients. A total of 69 CSF patients (39 males and 30 females, 38+/-8 years old) were randomized to take either P. niruri ( n=33) (450 mg capsules, td) or placebo ( n=36) for 3 months. Blood calcium, uric acid, citrate, magnesium, oxalate, sodium and potassium we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
13

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(76 citation statements)
references
References 11 publications
1
62
0
13
Order By: Relevance
“…Extracts of P. niruri were found to normalize high levels of urinary calcium, reducing the formation of calculus in patients (Nishiura et al, 2004). This suggests it interferes in the first stages of stone formation and may be an alternative in the treatment and/or prevention of urolithiasis and inhibit the formation of calcium oxalate crystals in the urinary tract, preventing renal calculus (Barros et al, 2003; Freitas, Schoe, Boim, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Extracts of P. niruri were found to normalize high levels of urinary calcium, reducing the formation of calculus in patients (Nishiura et al, 2004). This suggests it interferes in the first stages of stone formation and may be an alternative in the treatment and/or prevention of urolithiasis and inhibit the formation of calcium oxalate crystals in the urinary tract, preventing renal calculus (Barros et al, 2003; Freitas, Schoe, Boim, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…A Brazilian research group reported that intake of P. niruri reduces urinary calcium, based on the analysis of a subset of patients presenting with hypercalciuria (Nishiura et al 2004). An inhibitory effect of P. niruri extract on CaOx crystal growth and aggregation in human urine suggested that it might interfere with the early stages of stone formation and represent an alternative form of prevention for urolithiasis (Barros et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Estes pacientes apresentaram 38 ± 8 anos de idade, sendo 39 do sexo masculino e 30 do feminino. Os cálculos renais foram diadnosticados por ultrasonografia renal e raios-X abdominal (Nishiura et al, 2004). Observou-se o controle da hipercalciúria e leve redução de magnésio na urina, mas a quantidade e tamanho dos cálculos não sofreram qualquer alteração, bem como os parâmetros urinários.…”
Section: Phyllanthus Niruri: Estudos Clínicosunclassified